Role of Gypsum in Reclaiming Saline-Sodic Soils to Improving Soil Health and Enhancing Productivity (Journal of Agriculture and Biology, 2025)
Salinization and sodification of soil are a widespread concern, The United Nations Food and Agriculture Organization (FAO) reported that it affected 833 billion hectares of land worldwide. Gypsum is frequently utilized to restore saline-sodic and sodic soils due to solubility, cheap cost, availability, and simplicity of handling. The experiment was conducted at the experimental station of the Department of Land and Water Management, Faculty of Agricultural Engineering, Sindh Agriculture University, Tandojam, during the year 2021- 2022. The reclamation of saline-sodic soil under the influence of varying gypsum levels was investigated in a pot experiment. The research was set up in three replicated complete randomized designs (CRD), each with a total pot size of 30 x 30 cm (900cm2). G0 = 0 gypsum requirement (control treatment), G1 = 1/2 gypsum requirement, G2 = 1/3 gypsum requirement, and G3 = 1/4 gypsum requirement were the treatments prepared. After the leaching of water, the different soil properties were tested. According to the subject study, applying gypsum with various treatments reduced soil bulk density, dry density, water holding capacity, pH, EC, SAR, and ESP. The G1 was shown to be the most effective dosage among the various treatments because it lowers the maximum soil bulk density to 1.16 g/cm3 after leaching. Likewise, the overall maximum reduction in dry density, water holding capacity, pH, EC, SAR, and ESP after leaching was 1.42 g/m3, 27.07 %, 7.88, 3.21 dSm-1, 16.25 %, and 16 % for the same treatment and only increased the soil porosity to 56.22% after leaching. The application of G1=1/2 of the soil’s recommended gypsum dose appears to be the most cost-effective way to recover saline-sodic soil.